Effect of Expansion Technique of Uterine Incision at Caesarean Delivery on the Degree of Intraoperative Blood Loss - E. I. Nonye-Enyidah (Highlights on Medicine and Medical Research Vol. 4, 2021)
Background: Caesarean section is the most common major operation performed on women. Although caesarean section is much safe today due to improved techniques, anaesthesia, blood transfusion services and antibiotics, there are still major intra operative and post operative complications. Haemorrhage is one of the short term morbidities following caesarean section and may lead to maternal mortality. Aim: To determine which method of expansion of uterine incision at caesarean section (sharp and blunt) is associated with a reduction in blood loss. Methods: A prospective randomized study conducted among booked antenatal women admitted in antenatal ward for elective caesarean section at the University of Port Harcourt Teaching Hospital (UPTH) over a period of nine months. The eligible 354 women (177 for each group) were counseled for participation in the study and informed consent obtained. A profoma was prepared for each participant. Blood loss estimation (EBL) was undertaken using both volumetric and gravimetric methods. The data was collected and analyzed using EPI INFO statistical software. Results: The mean age of women in blunt group was 31.6 years and 31.7 years in sharp group. All the women had formal education. The mean parity in blunt group was 1.4 and 1.5 in sharp group. The mean gestational age for both groups was 38.1 (SD 1.0) weeks. The mean EBL during the study period was 594.4 (SD 167.0) mls. The mean EBL for sharp group was 602.3 (SD 176.6) mls and 586.4 (SD 157.3) mls for blunt group. The mean EBL for women in blunt group who had uterine extension was 889.3 (SD 100.3) mls while that of sharp was 944.4 (SD190.9) mls. Conclusion: Caesarean section is a common obstetric operation and needs to be made as safe as possible. Although sharp expansion of the lower segment transverse uterine incision resulted in more blood loss, the difference is not statistically significant. The difference in blood loss following inadvertent extension between the two groups is statistically significant. There was no need for a blood transfusion.